Application of Different Carbon Materials for Carbon Paste Electrodes to Simultaneous Electrochemical Detection of four DNA Bases with High Simpleness. Issue 8 (6th April 2018) - Zhu, Xiaping; Yuan, Yali; Zhang, Yun; Li, Jianping; Pan, Hongcheng
Abstract: Three different carbon materials, graphite, graphene and multiwalled carbon nanotubes (MWCNTs), were applied to fabricate carbon paste electrodes and used directly as working electrodes without any further modification in a simple electrochemical system for simultaneous detection of four DNA bases, guanine, adenine, thymine and cytosine. EIS and SEM were used to characterize the formed carbon paste electrodes made from different carbon nanomaterials and silicon oil, respectively. Conditions for bases detection were studied, such as ratio of carbon nanomaterials to silicon oil, types of buffer saline and pH. An unexpected result was discovered that compared with graphite and graphene, MWCNTs in carbon paste electrodes were not able to obtain admirable electrochemical behavior, the possible reason of which was preliminary discussed. Individual and simultaneous detection of four bases were successfully carried out, with acceptable linear ranges and low detection limits. Furthermore, this facile method had admirable reproducibility, stability and acceptable recovery in real urine sample (97.62 % ∼103.36 %), indicating certain practical potential. Abstract :